Ethnobotanical Study of Zingiberaceae Rhizomes as Traditional Medicine Ingredients by Medicinal Plant Traders in the Pancur Batu Traditional Market, North Sumatera, Indonesia - Marina Silalahi; Nisyawati; Endang C. Purba; Daichiro W. Abinawanto; Riska S. Wahyuningtyas (The Ethnobiological Society of Indonesia, 2021)
Traditional markets are places for buying and selling medicinal plants and are a source of ethnobotany research data. This study aims to determine the uses and characteristics of Zingiberaceae rhizomes have been used as traditional medicine and traded in the traditional market of Pancur Batu, North Sumatra. This research was conducted with an ethnobotany approach through surveys, interviews and observation participatory. The respondents are all medicinal plants traders in the Pancur Batu traditional market. The things that were asked of the traders included local names, special characters, benefits, and how to recognize the rhizome. The medicinal plant traders in the Pancur batu traditional market have been utilized and traded as many as 10 species of Zingiberaceae rhizome, most of them belonging Curcuma and Zingiber genera. The characteristics of rhizomes are recognized by traders through their size, color, and aroma. The cross-section of the rhizomes of each species is different in structure and color which is used as the main marker for each species. Rhizoma Zingiberaceae is used as the main ingredient for tawar (semi-solid medicinal herbs consumed by brewing), parem (solid medicinal ingredients), and oukup (traditional Karo sauna). The rhizome aroma of each species belonging Zingiberaceae is very distinctive which is related to the content of essential oils. The use of Zingiberaceae rhizomes as tawar and parem ingredients needs to be studied further so that they are developed into standardized herbs.